Volatility of exchange rates in selected new EU members: evidence from daily data - Jarko Fidrmuc; Roman Horváth (Center for Economic Studies and ifo Institute (CESifo), 2007)
We examine the daily exchange rate dynamics in selected new EU member states (Czech Republic, Hungary, Poland, Romania, and Slovakia) using GARCH and TARCH models between 1999 and 2006. Despite these countries adopted inflation targeting regime, they occasionally tried to manage their exchange rate. We find that the low credibility of exchange rate management implied higher volatility of exchange rates when it substantially deviated from the implicit target rates for all countries. Finally, we find significant asymmetric effects of the volatility of exchange rates in all analyzed countries.
Keywords: F31; C22; C23; 330; Wechselkurs; Volatilität; Inflation Targeting; Europäischer Währungsverbund; Target Zone; EU-Staaten (Osteuropa)